Information Communication Technology Tax Reforms and Tax Compliance in Rwanda Case of Rwanda Revenue Authority in Gasabo District (Global Journal of Management and Business Research, 2019)
The purpose of this study was to examine the contribution of ICT tax reforms in the tax compliance in Rwanda Taking Gasabo district as the case study. Objective: The objectives of the study were to assess the various ICT tax reforms and their contribution on tax compliance in Rwanda and to establish a relationship between ICT tax reforms and tax compliance in Rwanda. Descriptive and explanatory research design was used. The study population comprised of 128 employees of RRA from which 56 were selected using the Yemen's formula. Data was collected from both primary and secondary sources using questionnaire and documentation. The findings from the survey revealed that ICT tax reforms have contributed significantly on the tax compliance in Rwanda. The results further revealed a strong relationship between ICT tax reforms and tax compliance in Rwanda. The researchers recommended that although, a strong relationship between variables were identified, ICT tax reforms only contributes 56% on the tax compliance, other factors such as tax education and tax penalties should be enhanced to increase the tax compliance.
Keywords: ICT; tax reforms; tax compliance